THE EFFECT OF ENTREPRENEURIAL COMPETENCE AND ENTREPRENEURIAL MOTIVATION ON ENTREPRENEURIAL INTENTION: THE MEDIATING ROLE OF CREATIVITY AMONG STUDENTS OF UNIVERSITAS STIKUBANK - Atik Rakhmawati; Endang Tjahjaningsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines how entrepreneurial competence and entrepreneurial motivation shape students’ entrepreneurial intention, with creativity positioned as a mediating mechanism. Using an explanatory survey of Universitas Stikubank students who have taken entrepreneurship courses, the study finds that competence and motivation contribute to higher creativity. Entrepreneurial intention is strengthened primarily by motivation and by creativity, while competence does not translate into intention unless it is expressed through creative ideation and solution development. These findings highlight creativity as a key pathway through which capability and motivational drive are converted into entrepreneurial intention, offering implications for entrepreneurship education that integrates competence building with creativity stimulation and motivation support.